Distinguishing anaerobic digestion from electrochemical anaerobic digestion: Metabolic pathways and the role of the microbial community. (June 2023) - Wang, Nan; Yang, Yutong; Xu, Kunde; Long, Xiangang; Zhang, Yurui; Liu, Hongzhou; Chen, Tiezhu; Li, Jianchang
Abstract: In this study, we explored why electrochemical anaerobic digestion (EAD) results in higher methane conversion and lower CO2 emissions than anaerobic digestion (AD). Single-chamber AD and EAD reactors were used in this experiment, and the temperature was set as the disturbance factor. Current, pH, electrode potential, gas content, and microbial community were used as indicators for our analysis. Flux balance analysis (FBA) and high-pass next-generation sequencing (NGS) were used to explore the relationships between AD and EAD methane-producing metabolic fluxes and microorganisms. The results showed that the average methane fluxes were 22.27 (AD) and 29.65 (EAD). Compared with AD, EAD had improved hydrogen-dependent CO2 reduction pathway. Trichloromonas was the dominant electricity-producing microorganism on the EAD anode film, which was closely related to the H2 flux at the cathode. Oscillibacter and Syntrophomonas were the dominant bacteria in the fermentation broth, specific to EAD. The abundance of Oscillibacter was positively correlated with the H2 flux, and the presence of Oscillibacter enhanced CO2 reduction by hydrogen. Methanosaeta was the only dominant methanogenic bacterium in AD and EAD, and its abundance was higher in the experimental group with a greater methane flux. Graphical abstract: Image 1 Highlights: EAD and AD methanogenic metabolic fluxes were analyzed. The EAD is richer in microbial species and has higher biodiversity. Trichloromonas on EAD anode film is electricity-producing microorganism. Oscillibacter enhances the hydrogen reduction CO2 pathway.